Bibliographic and Intellectual Control: why it matters - Newton, Cate (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
When the Cellulose Acetate Microfilm forum was set up just over two years ago one of its first activities was to carry out in-depth surveys of the condition of microfilm in the collections of the libraries involved. To a greater or lesser degree the libraries found evidence of deterioration in their stocks of acetate film. Many libraries, especially those which had collections dating from more recent decades, had no significant problems with the condition of the microfilm stock in their care. But for almost all of the libraries there was a secondary aftershock, as it were, after the first earthquake. This shock came to those who are responsible for listing and cataloguing the materials, and showed up considerable gaps in the recording of details of the surrogate microfilms in the library collections. In this paper I will describe the extent of the problem, suggest the causes and possible solutions, and conclude with a look towards some strategic possibilities for coping in the future.